Fluoride-modified implant surfaces improves osseointegration in the tibias of rats with induced diabetes - Lopes de Oliveira, Guilherme José Pimentel [UNESP] (2023)
This study evaluated the influence of a fluoride-modified titanium surface on osseointegration in rats with induced diabetes. One hundred and eighty rats were randomly allocated into 3 groups with 60 animals each: Control group (C): Animals without diabetes; Diabetes Group (D): Animals with uncontrolled induced diabetes; Controlled Diabetes Group (CD): Animals with diabetes induced controlled by the insulin administration. Diabetes was induced by streptozotocin injection. Each animal received 2 implants in the proximal tibial metaphysis, one with the machined surface (M) and the other one with a fluoride-modified titanium surface (F), after 4 weeks of induction of diabetes. The animals were submitted to euthanasia 2, 4, and 6 weeks after the implant placement (n = 20 animals/group). The osseointegration was evaluated by the implant removal torque test and the histometric analysis of the nondecalcified histological sections: 1) Contact bone/implant (%BIC); 2) Bone tissue area between implant threads (%BBT). Implants with F surface showed a higher removal torque than implants with surface M in all groups. There was no difference in %BIC between the groups regardless of the surface used. The F surface showed a tendency to present higher %BBT values for the 3 evaluation periods in the D group. The fluoride-modified implant surface has no impact on the %BIC and %BBT. However, the fluoride-modified implant surface increases the locking of the implants with the bone. The hyperglycemia was associated with lower removal torque values despite the surfaces of the implant used.